Perbandingan Hasil Belajar Matematika dengan Structured Dyadic Method dan Brain Gym Method - Bayu Chendi Saputra; Arif Rahman Hakim (Universitas Indraprasta PGRI, 2017)
The purpose of this research is to determine difference between mathematics achievement by using structured Dyadic method and Brain GYM method. This research used quasy experiment method. Population of this research is all the students of SMP Islam Malahayati at even semester in 2015/2016. Affordable population is all the students of class VII and the sample is 24 students of VII D and 23 students of class VII E taken by random sampling. Before hypothesis test, the data fulfill a series test i.e. normality by liliefors test and homogeneity test by fisher test. The result of normality test, both of class in normal distribution, and the result of homogeneity test the varian of both class is homogen. Based on data analyze in the form of t test, ?=0.05 from both of class t test is 2.1025 and t table is 2.0158. it can be concluded that there are difference of student’s mathematics achievement by using structured dyadic method and Brain Gym method.